HUBUNGAN BUDAYA ORGANISASI DENGAN KINERJA GURU DI TK KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Putri Ayu; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was aimed to know the correlation of organizational culture and teachers performance Kindergartens in Simpang Baru Village Tampan Sub District Pekanbaru City. The population of this research is Kindergartens in Simpang Baru Village as many 74 people compirising teachers from 12 Kindergartens. Given the small population the researchers determined the entire population becomes saturated sample of sampling. Method of this research is Person Product Moment correlation to know the correlation of organizational culture and teacher performance. The technique of collecting data used questioner in Likert scale form. The technique of analyzing data used scale test and statistic analytical by using SPSS program for Windows Ver. 16. Based on hypothesis there is any significant positive the correlation of organizational culture and teachers performance Kindergartens in Simpang Baru village Tampan sub District Pekanbaru City. It could be seen from the result of correlation that rxy=0,817 and significant level 0,000<0,05. The level of correlation organizational culture and teachers performance is in the very strong category with the rank of determinant coefficient in the amount 66,8%, it means that organizational culture affect teachers performance .Key words : Culture Organizational, Teachers Performance